Nanoencapsulation of n-octadecane phase change material with silica shell through interfacial hydrolysis and polycondensation in miniemulsion. (15th December 2015) - Liang, Shuen; Li, Qianbiao; Zhu, Yalin; Chen, Keping; Tian, Chunrong; Wang, Jianhua; Bai, Ruke
Abstract: Nanoencapsulation of n-octadecane phase change material with silica shell was performed through interfacial hydrolysis and polycondensation of tetraethyl orthosilicate in miniemulsion. The chemical composition and crystallinity of the synthesized n-octadecane@SiO2 nanocapsules were characterized by FT-IR spectroscopy and XRD analysis. DSC (differential scanning calorimetry) and TG results demonstrated that the as-prepared nanocapsules have high heat storage capability and good thermal stability. The melting enthalpy and encapsulation ratio of the nanocapsules were as high as 109.5 J g −1 and 51.5%, respectively. Most importantly, n-octadecane@SiO2 nanocapsules with different morphologies and sizes (169–563 nm) have been conveniently obtained via tuning water-to-ethanol ratio in continuous phase of the miniemulsion. With decreasing size of the n-octadecane@SiO2 nanocapsules, the phase change temperatures move to lower values due to Gibbs–Thomson effect. Moreover, the as-prepared nanocapsules possess high thermal conductivity, and can maintain their phase transition properties perfectly after 500 melting–solidifying thermal cycles, making them ideal candidates as thermal energy storage materials. Graphical abstract: Highlights: Nanoencapsulated n-octadecane with silica shell was prepared in miniemulsion. The nanocapsules present a well-defined spherical core–shell structure. Sizes of the nanocapsules can be conveniently tuned by water-to-ethanol ratio. Phase change properties of the nanocapsules are size dependent.